Women of the Washington Press Politics, Prejudice, and Persistence - Beasley, Maurine H. (Northwestern University Press, 2012)
Winner, 2012 Frank Luther Mott-Kappa Tau Alpha Research Award. Women of the Washington Press argues that for nearly two centuries women journalists have persisted in their efforts to cover politics in the nation's capital in spite of blatant prejudice and restrictive societal attitudes. They have been held back by the difficulties of combining two competing roles - those of women and journalists. As a group they have not agreed among themselves on feminist goals, while declaring that they aspire to be seen as professional journalists, not as advocates of a particular ideology. Still, they have brought a different perspective to the news, as they have fought hard to prove that they are capable of covering political issues just like male journalists. Over the years women have networked with each other and carved out areas of expertise - such as reporting of politically-oriented social events and coverage of first ladies - that men disdained, while they pressed to gain entrance to sex-segregated institutions like the National Press Club. Attempting to merge the personal and the political, they have raised issues like sexual harassment that men journalists left untouched. At a point today where they represent about half of accredited correspondents, women still face shifting barriers that make it difficult to combine the roles of both women and journalists in Washington, but they are continuing to broaden the definition of political journalism.